Modelagem matemática e simulação numérica da deposição de partículas em duto horizontal - Cruz, Suellen Freire Rigatto da (2018)
Oil will remain the largest source of fuel in the coming years. However,during the oil extraction appear some problems such as the scale formation in the various stages of the production process. The scale problem, which occurs from the deposition process,reduces all or part of the flow conduits, increasing the pressure drop and reducing the oil production. The particles depositionrepresentsa significant problem in the oil and gas industry, therefore research in this area is of great relevance.In this paper,the particles deposition,in a turbulent and biphasic flow,inside of a horizontal pipe was modeled, with the software Ansys Fluent®,using the approach Euler-Lagrange with the Dense Discrete Phase Model(DDPM)and the approach Euler-Granular.Due to the high computational cost due to the large number of injected particles, the results show that the approach Euler-Lagrange with the model DDPM is not appropriate to calculate problems involving dense flows, being more appropriate the approach Euler-Lagrange. The study also shows the influence of some parameters atthe particles depositionprocess. The increases in particle deposition rates are directly proportional to increases at the pipe wall roughness and particle diameter. The results also show values of computational time, velocity and volumetric fraction of particles that allow a better visualization of the deposition phenomenon for a required computational time feasible for the computational system used.